The relation between serum neurofilament light chain levels and disease severity in multiple sclerosis: insights from an Egyptian study - Hagar S. Ali; Ayman M. Nasef; Lobna M. ElNabil; Mohamed M. Fouad; Shaimaa S. Khater (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Serum neurofilament light chain (sNFL) is a neuronal protein released during damage to the central nervous system (CNS) and its axons. Elevated levels of sNFL in patients with multiple sclerosis (MS) are linked to greater disease severity, an increased number of relapses, and a reduction in cerebrospinal fluid (CSF) volume. However, the effectiveness of sNFL in monitoring disease progression in real-world MS patients requires further evaluation. Results This prospective, single-center cohort study involved 76 patients who met the 2017 revised McDonald criteria and were followed for one year, from January 2022 to June 2023. Baseline evaluations included clinical assessments using the Expanded Disability Status Scale (EDSS), serum NFL levels, brain and spine MRI scans, and cerebrospinal fluid (CSF) analysis. Serum NFL levels were measured using the enzyme-linked immunosorbent assay (ELISA), and these levels were compared with clinical and MRI variables through univariable analyses. This study had a mean (SD) age of 29 ± 8.1 years, with 77.6% females. Sensory symptoms (68.42%) and pyramidal signs (64.47%) were predominant. MRI revealed periventricular lesions in 80.26% of patients, and 72% had > 10 oligoclonal bands in CSF. Baseline levels of sNFL were measured with a mean of 11.32 pg/mL (SD ± 6.92) and showed significant associations with several clinical features: pyramidal symptoms (p = 0.002), periventricular lesions (p = 0.02), spinal cord lesions (p < 0.001), and a higher T2 lesion burden (p < 0.001). Elevated levels of sNFL were predictive of increased EDSS scores at the one-year follow-up (p = 0.01). However, no correlation was found between sNFL levels and either patient age (p = 0.3) or gender (p = 0.4). Conclusion sNFL levels reflect disease severity and progression in newly diagnosed MS patients, correlating with clinical disability and radiological markers of neuronal damage. These findings support sNFL as a valuable biomarker for assessing MS prognosis and monitoring along with MRI biomarkers.